(untitled) (EAAE Annual Conference Proceedings, 2023)
Krater (ENG. crater) is an ecosystem, a production laboratory, and a practice of composting anthropocentric perceptions of what it means to work and learn while cultivating ground for difficult questions. Krater community sprouted from the neglected, crater-like construction site near the city center of Ljubljana, Slovenia, in 2020. Krater’s urban grounds interconnect more than 200 species and represent an irreplaceable ecological corridor between the city’s eastern and western forests.